Older people's experiences of therapeutic exercise as part of a falls prevention service: survey findings from England, Wales and Northern Ireland. (28th November 2013) - Buttery, Amanda K.; Husk, Janet; Lowe, Derek; Treml, Jonathan; Vasilakis, Naomi; Riglin, Jackie
Abstract: Introduction: falling, and fear of falling, significantly affect older people and their lifestyle resulting in loss of confidence, restriction of activity and deteriorating quality of life. Multi-factorial assessment and active participation in an evidence-based exercise programme are key interventions to prevent and manage falls. Objective: to examine older people's experiences of therapeutic exercise as part of a falls prevention service in NHS Trusts in England, Wales and Northern Ireland. Methods: a cross-sectional survey targeted patients and staff members delivering exercise interventions for reducing falls. A multi-disciplinary group including patient and staff representatives developed a 20-item patient questionnaire and a 12-item staff questionnaire that were distributed to 94 NHS Trusts (113 participating sites within the NHS Trusts) in October 2011. Results: response was 57% for the patient sample and 88% for the staff sample. The median (IQR) age of patients was 82 (77–86) years. 72% were women. Two-thirds reported attending group-based therapeutic exercise classes generally of short duration (80% <12 weeks) and low intensity (85% one class per week) at hospitals and community venues. Balance and strength exercises were prescribed; 68% reported using resistance equipment such as ankle weights and/or exercise band. Only 52% reported exercises were made more difficult as they improved. However, patient satisfaction levels were high (95% satisfied or very satisfied). Patients and staff reported limited availability of strength and balance follow-up classes. Conclusion: despite high levels of patient satisfaction therapeutic exercise provision was limited and implementation of evidence-based exercise interventions by healthcare providers is incomplete and varies widely. Patients and staff wanted greater availability of long-term exercise services for falls prevention.